2017
DOI: 10.1002/ajhb.22961
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, inflammatory, and ecological correlates of maternal retinol allocation to breast milk in agro‐pastoral Ariaal communities of northern Kenya

Abstract: Objectives Vitamin A (VA) is an essential micronutrient required for a range of biological functions throughout life. VA deficiency (VAD) claims an estimated 1 million preschool children’s lives annually. Human milk is enriched with VA (retinol) from the maternal blood, which originates from the hepatic reserve and dietary intake. Secreting retinol into milk will benefit the nursing infant through breast milk, but retaining retinol is also important for the maternal health. Previous studies found that the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In the original study, data were collected from consenting mothers under approval of the community chiefs and the institutional review boards of the University of Washington and Kenya Medical Research Institute. Data collection took place during a prolonged drought and food shortage; many mothers were coping with the food shortage by reducing food variety, meal size or the number of meals for their consumption (Apland & Fujita, , , ; Apland, Fujita, & Chang, ; Fujita, ; Fujita, Apland, & Chang, ), and prioritizing their children in allocating limited amount of foods within households (Fujita, ). Our subsequent research found that low BMI (Fujita, ; Fujita, Brindle, Lo, Castro, & Cameroamortegui, ), vitamin A deficiency (Fujita, ; Fujita et al, ; Fujita, Lo, & Brindle, ), and iron deficiency (Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita & Wander, ) were prevalent among these mothers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the original study, data were collected from consenting mothers under approval of the community chiefs and the institutional review boards of the University of Washington and Kenya Medical Research Institute. Data collection took place during a prolonged drought and food shortage; many mothers were coping with the food shortage by reducing food variety, meal size or the number of meals for their consumption (Apland & Fujita, , , ; Apland, Fujita, & Chang, ; Fujita, ; Fujita, Apland, & Chang, ), and prioritizing their children in allocating limited amount of foods within households (Fujita, ). Our subsequent research found that low BMI (Fujita, ; Fujita, Brindle, Lo, Castro, & Cameroamortegui, ), vitamin A deficiency (Fujita, ; Fujita et al, ; Fujita, Lo, & Brindle, ), and iron deficiency (Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita, Paredes Ruvalcaba, Wander, Corbitt, & Brindle, ; Fujita & Wander, ) were prevalent among these mothers.…”
Section: Methodsmentioning
confidence: 99%
“…Milk and blood sample collection methods have been described in depth elsewhere (Fujita, ; Fujita et al, , Fujita & Wander, ). In brief, breast milk collection took place following an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same for anemia include BMI, age, parity, breastfeeding status, and inflammation/infectious disease (Alene & Mohamed Dohe, ; Antelman et al, ;Bodnar, Scanlon, Freedman, Siega‐Riz, & Cogswell, ; Semba et al, ). These variables except milk volume were available from our previous research (Fujita, ; Fujita et al, , , ; Fujita, Brindle, Lo, Castro, & Cameroamortegui, ; Fujita & Wander, ; Stone & Fujita, ) and utilized as covariates to adjust for their effects on milk characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The research on the associations between maternal inflammation/infection and milk components is inconsistent. Some studies suggest that maternal inflammation/infection may alter milk fatty acids or immune components (Gardner et al, ; Groer, Davis, & Steele, ; Mizuno et al, ), whereas others found no associations of subclinical inflammation with milk micronutrients (Fujita, Lo, & Brindle, ; Zavaleta et al, ).…”
Section: Introductionmentioning
confidence: 99%